TINJAUAN YURIDIS FENOMENA DERET TUNGGU TERPIDANA MATI BERDASARKAN HUKUM HAK ASASI MANUSIA INTERNASIONAL - Asfadila, Shafira; Deliana HZ, Evi; Diana, Ledy (JURNAL HUKUM DAS SOLLEN, 2024)
Many death row inmates spend years even decades before finally being executed, so that in the practice they not only receive the death penalty, but also imprisonment as an additional punishment. The large number of death row prisoners serving sentences in prisons, globally, causes another problem, namely there is a psychological disturbance in death row prisoners caused by several factors such as conditions in detention, to the pressure of waiting for execution whose time never comes. This is globally called the death row phenomenon. This research uses normative legal methods, which are carried out on various rules of international law, especially the relationship between the death row phenomenon and the Convention Against Torture and other Cruel. Research specifications are descriptive analytical. The data source used is secondary data from library materials that include primary and secondary legal materials. The results showed that international human rights law prohibits torture, which in this case includes psychological torture. This has been enshrined in the Convention Against Torture and Other Cruel. In addition, judging from other international human rights law clauses, the delay of execution with various other factors such as the state of prisons and detention centers in the countries that still impose the death penalty, which causes the deathrow phenomenon, can be considered a violation of international human rights law, although it is not stated descriptively.